2019
DOI: 10.1007/s10877-019-00341-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of oxygen reserve index (ORi™) to avoid excessive hyperoxia during general anesthesia

Abstract: The Oxygen Reserve Index (ORi™) is a non-invasive variable that reflects oxygenation continuously. The aims of this study were to examine the relationship between arterial partial pressure of oxygen (PaO 2 ) and ORi during general anesthesia, and to investigate the usefulness of ORi as an indicator to avoid hyperoxia. Twenty adult patients who were scheduled for surgery under general anesthesia with arterial catheterization were enrolled. After induction of general anesthesia, inspired oxygen concentration (Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 19 publications
(27 reference statements)
1
54
1
Order By: Relevance
“…[13][14][15][16] ORi is a parameter-driven from this device that is between 0 and 1 values, and it is sensitive to the changes in arterial oxygenation in the blood, with the range of 100 to 200 mmHg. [2,[8][9][10]13,[18][19][20][21] When oxygenation is in the moderate hyperoxic content showing an arterial blood oxygenation value of 100-240 mmHg in arterial blood gas analysis, the pulse oximeter SpO2 value remains 100%, whereas there is a decrease in the value of ORi. [2,[18][19][20][21] In our study, Figure 1 and Table 4 provides data on timedependent correlations between ORi with SpO2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] ORi is a parameter-driven from this device that is between 0 and 1 values, and it is sensitive to the changes in arterial oxygenation in the blood, with the range of 100 to 200 mmHg. [2,[8][9][10]13,[18][19][20][21] When oxygenation is in the moderate hyperoxic content showing an arterial blood oxygenation value of 100-240 mmHg in arterial blood gas analysis, the pulse oximeter SpO2 value remains 100%, whereas there is a decrease in the value of ORi. [2,[18][19][20][21] In our study, Figure 1 and Table 4 provides data on timedependent correlations between ORi with SpO2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hyperoxemia is a potent vasoconstrictor stimulus to the coronary circulation, functioning at the level of the microvascular resistance vessels. [20,21] Tsuchiya et al demonstrated that the PVI could be used to evaluate anesthesia-induced hypotension in patients undergoing general anesthesia without age group classi cation. [23] This technique has been used in patients undergoing mechanical ventilation in the intensive care unit to detect uid responsiveness through respiratory patterns and peripheral perfusion changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vos et al investigated the correlation between PaO 2 and ORi during the administration of oxygen in 20 healthy volunteers, and they also reported that the two values have a strong positive correlation [24]. In addition, regarding the correlation between PaO 2 and ORi during anesthesia under oxygenation, when PaO 2 was less than 240 mmHg (n = 69), linear regression analysis showed a relatively strong positive correlation (r 2 = 0.706) [25].…”
Section: What Is Orimentioning
confidence: 99%
“…In addition, hyperoxia can be detected by monitoring ORi in patients under general anesthesia, and thus the administration of unnecessarily high concentrations of oxygen can possibly be avoided. In fact, there are several reports demonstrating that the use of ORi in managing oxygen levels during and after surgery, and for patients in the intensive care unit (ICU) can prevent exposure to excess oxygen [25,48,49]. In general, high oxygen concentrations are more harmful to infants, children, and older patients than to adults [50].…”
Section: • Pediatric Applicationsmentioning
confidence: 99%